IMPROVED CAPACITY FOR REAL-TIME VIDEO WATERMARKING - Shahidah Mahbob, author; Azizah Abd. Manaf, Prof.Dr., supervisor; Sekolah Informatik Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2012)
Thesis